Forecast of Agricultural Production in Ukraine Under Martial Law: Results of the Regression Analysis - Byrkovych, Tatiana; Yakymchuk, Yuriy; Pakharenko, Olha; Suduk, Olena (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
Due to Russia’s aggressive invasion, Ukraine is losing not only infrastructure and industrial facilities, but also sown areas. This situation will have a negative impact on food security not only in Ukraine, but also in Europe, the Middle Eastm and North Africa. According to official data of the State Statistics Service of Ukraine, regional military administrations, and from open sources, in 2022 Ukraine could not sow a significant area of crops, which according to authors’ estimates could be 75%, 50%, or 25%. Therefore, the issue of providing agricultural products not only to Ukraine, but also to partner countries that import Ukrainian grains, vegetables and other crops is of practical interest. It is obvious that crop losses are significant if 75%, 50%, or 25% of the lands of a particular region are active in combat, and it is impossible to conduct a sowing campaign. The relationship between the volume of production (gross harvest) of cereals and legumes and their sown area on the basis of many years of research has been done on the basis of correlation-regression modeling for more than thirty years. According to FAO estimates, between 20% and 30% of fields used for growing crops in Ukraine, such as winter cereals, maize, or sunflower, may not be sown or will remain unharvested during the 2022-2023 season. In addition, crop yields are expected to decline by 10% due to the delayed or missed fertilizer application times, inability to control possible diseases, pests, delayed harvesting, lack of manpower or infrastructure capacity for autumn harvesting. According to Ukrainian experts, in 2022 the sown area in Ukraine is 78% of last year’s figures, and the total area under crops decreased by 2.5 million hectares. In this work. made on the basis of an analytical method, the forecast of productivity in the conditions of military aggression of Russia against Ukraine at change of sown territories has been formed. Management of agriculture is now an important area that covers not only the science of food production, but also the practical activities of creating an agricultural product. A set of measures for economic stimulation of agricultural cultivation of important crops has been developed, the foundations for the development of partnership between the government and agricultural business and the population have been formed. The best principles of decentralization reform, such as the Republic of Poland in the field of agricultural production, have been applied.